An Integrated marketing communications campaign for Debu by Juan Carlo - Bellare, Shane Aldrin M. (Animo Repository, 2014)
Backed up by Juan Carlo the Caterers 19 years of catering experience, innovations in operations and equipment and an extensive network of complementary suppliers, Debut by Juan Carlo was born in 2013 with the goal of having a one-stop-shop catering brand that offers the most memorable debut experience with premium food, elegant displays, and customizable options for amenities. Their packages were developed specifically for debuts, as a result of consultation, research and interviews with actual debutantes. Competition is fierce and intense as the brand is not only going up against other premiere debut caterers, but also with Event Venues and Event Organizers that offer similar debut packages. It is worth noting that Debut by Juan Carlo is the only debut caterer that offers two sets of debut packages menu based and amenities based. We will go into detail later when we discuss each competitors debut packages. In terms of promotions, majority of the marketing and advertising budget will go into digital and events, with support from print, sales promotion and direct marketing. According to the brand, the debut is the single most important rite of passage for a young woman, next to marriage. The strategy is to create an aspirational thematic campaign that communicates the magical experience of the debut through the use of celebrity debutantes such as Kathryn Bernardo and Julia Barretto. These popular teen celebrities best represent the target market as they have the admirable qualities of being fun-loving and adventurous young ladies but with the right amount of elegance and class. We want the target market to feel that they can also experience the kind of debut that their idols have experienced - the grandest, most beautiful, most unique debut. It is what they've always dreamed about. The primary objectives of this campaign are to create brand awareness, generate leads and increase sales through various marketing channels that are relevant to the target audience. As for the scope and limitations, the study will only feature Metro Manila-based Debut Caterers who are members of the Food Caterers Association of the Philippines. The focus is Metro Manila because in 2011, the National Capital Region accounted for 24.2% of the countrys expenditure (Euromonitor International, 2013). This means that the population is able to afford such premium debut packages.